Earnings inequality in Germany - Abraham, Katharine G. 1954-; Houseman, Susan N. 1956- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1993)
Recent studies have documented the growth of earnings inequality in the United States during the 1980s. In contrast to these studies' findings, our analysis of micro data for the former West Germany yields virtually no evidence of growth in earnings inequality over the same period. Between 1978 and 1988, a reduction in the dispersion of earnings among workers in the bottom half of the earnings distribution led to a narrowing of the overall dispersion of earnings in Germany. Earnings differentials across education and age groups remained roughly stable, and there was no general widening of earnings differentials within either education or age groups. Germany wage setting institutions tend to limit earnings differentials across groups of workers, but differences in wage setting institutions cannot fully explain the differences between trends in earnings inequality in Germany and those in the United States. Both the high quality of the training received by non- college-bound German youth and the fact that the growth of the highly- educated work force did not decelerate in Germany as it did in the United States seem likely to have contributed to these differences.